The individualized music therapy assessment profile as an initial assessment tool of social emotional functioning - Salokivi, Maija (2012)
An assessment in music therapy clinical practice is an essential part of the therapy process.Based on the assessment the therapist is able to recognize the needs of the client and plan the influential interventions in the therapy. A music therapy assessment evaluates a client´s individual strengths and weakness in both musical and non-musical areas.